Protein-Assisted Assembly of Modular 3D Plasmonic Raspberry-like Core/Satellite Nanoclusters: Correlation of Structure and Optical Properties - Hoeller, Roland P. M.; Dulle, Martin; Thomae, Sabrina; Mayer, Martin; Steiner, Anja Maria; Foerster, Stephan; Fery, Andreas; Kuttner, Christian; Chanana, Munish (ACS nano, 2016)
We present a bottom-up assembly route for a large-scale organization of plasmonic nanoparticles (NPs) into three-dimensional (3D) modular assemblies with core/satellite structure. The protein-assisted assembly of small spherical gold or silver NPs with a hydrophilic protein shell (as satellites) onto larger metal NPs (as cores) offers high modularity in sizes and composition at high satellite coverage (close to the jamming limit). The resulting dispersions of metal/metal nanoclusters exhibit high colloidal stability and therefore allow for high concentrations and a precise characterization of the nanocluster architecture in dispersion by small-angle X-ray scattering (SAXS). Strong near-field coupling between the building blocks results in distinct regimes of dominant satellite-to-satellite and core-to-satellite coupling. High robustness against satellite disorder was proved by UV/vis diffuse reflectance (integrating sphere) measurements. Generalized multiparticle Mie theory (GMMT) simulations were employed to describe the electromagnetic coupling within the nanoclusters. The close correlation of structure and optical property allows for the rational design of core/satellite nanoclusters with tailored plasmonics and well-defined near-field enhancement, with perspectives for applications such as surface-enhanced spectroscopies.
CRIS-Team Scopus Importer:2023-03-20
Keywords: electromagnetic modeling; generalized multiparticle Mie theory (GMMT); nanoparticle assembly; plasmonic coupling; Protein-coated gold and silver nanoparticles; small-angle X-ray scattering (SAXS)